Measurements of the Higgs boson inclusive and differential fiducial cross-sections in the diphoton decay channel with pp collisions at s $$ \sqrt{s} $$ = 13 TeV with the ATLAS detector. (Tufts University. Tisch Library., 2022)
Keywords : Hadron-Hadron Scattering, Higgs Physics.; Springer Open.